Use of modern innovative nanotechnologies for performinghigh-aesthetic dental restorations - Коленко, Ю. Г.; Литвин, Т. В. (Actual Dentistry, 2019)
Summary. The article deals with the aesthetic restoration of teeth using the universal nanohybrid highly aesthetic composite restoration material Jen-Favorite LC. It is shown that the modern level of development of aesthetic dentistry allows each patient who applies to the clinic not only to cure teeth or gum disease, but also to improve aesthetic parameters. Key words: aesthetic restorations, frontal teeth, composite, Jen-Radiance.